2003
DOI: 10.1128/iai.71.2.717-725.2003
|View full text |Cite
|
Sign up to set email alerts
|

Oral Treponemes and Their Outer Membrane Extracts Activate Human Gingival Epithelial Cells through Toll-Like Receptor 2

Abstract: Oral treponemes are considered to be important in the development and progression of periodontal diseases. We investigated the mechanisms of recognition and activation of human gingival epithelial cells (HGEC) with the oral treponemes Treponema denticola, Treponema vincentii, and Treponema medium and their outer membrane extracts (OMEs). T. vincentii and T. medium but not T. denticola produced interleukin 8 (IL-8) in an HGEC culture. Further, all three treponemes induced IL-8 mRNA expression and NF-B activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
61
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 56 publications
2
61
0
Order By: Relevance
“…In this context, future studies should focus on determining the involvement of the TLRs in MspA or MspTL recognition and mapping the common regions of the Msps that recognize and transduce the signal to stimulate the host cells to secrete ICAM-1 and the proinflammatory cytokines. Interestingly, outer membrane extracts of T. denticola, T. vincentii, and Treponema medium stimulated IL-8 production in the human gingival epithelial cells, which appeared to be mediated through Toll-like receptor 2 (2).…”
Section: Vol 73 2005 Induction Of Icam-1 and Cytokines By Spirochetmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, future studies should focus on determining the involvement of the TLRs in MspA or MspTL recognition and mapping the common regions of the Msps that recognize and transduce the signal to stimulate the host cells to secrete ICAM-1 and the proinflammatory cytokines. Interestingly, outer membrane extracts of T. denticola, T. vincentii, and Treponema medium stimulated IL-8 production in the human gingival epithelial cells, which appeared to be mediated through Toll-like receptor 2 (2).…”
Section: Vol 73 2005 Induction Of Icam-1 and Cytokines By Spirochetmentioning
confidence: 99%
“…The surface molecules that showed enhanced IL-8 secretion were P. gingivalis gingipain-R (40), a glycoprotein fraction in the cell surface from P. intermedia (48), and a capsular polysaccharide from Actinobacillus actinomycetemcomitans (39). Several oral treponemes have been reported to stimulate proinflammatory cytokines in various cell types, such as gingival fibroblasts and gingival epithelial cells (2,25,37,43). However, with the exception of their LPS or LPS-like materials, none of them has been analyzed at the molecular level.…”
Section: Vol 73 2005 Induction Of Icam-1 and Cytokines By Spirochetmentioning
confidence: 99%
“…Recent reports implicate Msp in the disruption of fibroblast calcium responses and cytoskeletal assembly (1,3). PrtP activity contributes to T. denticola tissue penetration (4,12) and modulation of inflammatory cytokine responses (2,5). PrtP is reported to either contribute to (15) or interfere with (21) T. denticola binding to Porphyromonas gingivalis.…”
mentioning
confidence: 99%
“…The ability of the host to recognize and initially respond to microbes as well as microbial components has been largely attributed to a family of type I transmembrane Toll-like receptors (TLRs) (20,34,38). Previous studies analyzing how T. denticola stimulates innate immune responses have demonstrated that T. denticola can stimulate human gingival epithelial cells (HGECs) through TLR2 (3). However, the functional significance of other TLRs involved in mediating cellular responses to T. denticola and how this recognition mediates qualitative and quantitative aspects of the host inflammatory response are currently not well understood (29).…”
mentioning
confidence: 99%